Gene Expression Profile And Modulation Of Genetic Pathways In Acute Myeloid Leukaemia T(8;21) - Bashanfer, Salem Ali Alsalem (2013)
Many in vivo and in vitro models have been widely used in experimental research in order to facilitate pathway analysis, gene targeting and further scientific discoveries. Cell lines, such as Kasumi-1 and SKNO-1, have been used to study the AML1/MTG8 mechanisms in acute myeloid leukaemia t(8;21). However, in some cases, results obtained from in vivo and in vitro studies are incompatible or not valid when applied on patients. Given the above, the primary aim of this study is to explore and identify the similarities and differences of gene expression profiles of AML t(8;21) patient samples and the corresponding cell lines (Kasumi-1 and SKNO-1) as compared to normal CD34 cells. The initial analysis revealed that there were 34,073 differentially expressed genes found in patient samples and the corresponding cell lines as compared to the control cells, with a Spearman Rho correlation coefficient of 0.451 between the patient samples and cell lines. However, the 6,092 overlapping differentially expressed genes (3,297 upregulated) and (2,795 downregulated) between patient samples and the corresponding cell lines had a Spearman Rho correlation coefficient of 0.826. These overlapping genes were then subjected to further analysis. The analysis comprised of hierarchical clustering, gene ontology and functional annotation clustering as well as pathway analysis using two different software packages (GeneSpring v11.5 and DAVID v6.7). The aim of the analysis was to identify the function of those genes and pathways implicated within.